PENGARUH DIGITALISASI PERBANKAN TERHADAP KEPUASAN NASABAH BANK MANDIRI KCP SOLO URIP SUMOHARJO - Nurul Hikmatul Arofah; Ahmad Husin; Ngaisah (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the effect of banking digitalization on customer satisfaction of Bank Mandiri KCP Solo Urip Sumoharjo. This study covers the field of banking digitalization. The population of this study was 932 customers of Bank Mandiri Solo Urip Sumoharjo Branch Office. The sample in this study was 100 people, meaning 100/932 = 0.107 if the percentage is 10.7%. This can be said that the sample has met the minimum sampling standards. The sampling technique uses random sampling or random sampling. Data collection used in this study is using documentation and questionnaires personally. The analysis was carried out using SPSS. So for the first hypothesis There is an influence of Automatic Teller Machine on Customer Satisfaction at Bank Mandiri Solo Urip Sumoharjo Branch Office is proven true. So for the second hypothesis there is an influence of i-Banking on Customer Satisfaction at Bank Mandiri Solo Urip Sumoharjo Branch Office is proven true. So for the third hypothesis There is an influence of m-Banking on Customer Satisfaction at Bank Mandiri Solo Urip Sumoharjo Branch Office is proven true. So the fourth hypothesis states